Autistic Spectrum Disorder Screening in Kindegarten Children from two Schools in Arequipa - Talavera Lacunza , Priscilla Elizabeth (2022)
This research sought to describe the epidemiological characteristics of a ASD screening applied to children aged 3 to 5 years from two schools. The population was made up of 318 students (158 students from a private school and 160 students from a public school). The Modified Checklist for Autism in Toddlers –with Follow-Up (M-CHAT/F) was used as instrument, and once completed by the parents, it was verified by observing each child. We obtained that: 28 children, that is, 10 % of the population, obtained a positive score on the questionnaire. From this percentage we had that: 50 % were 3 years old, 17.86 % were 4 years old and 32.15 % were 5 years old. 92.86 % were males while only 7.14 % were females. The item with the lowest positive frequency for ASD was number 16 ("Does your kid walk?") and the item with the highest positive frequency for ASD was number 22 ("Does your child sometimes stare at nothing or wander with no purpose?") Only six children continued to score positively after the follow-up interview, representing 21.43 % of the children with a positive score on the questionnaire in the first stage.